Fiber optic coupled survey meter for NORM and low-level radioactivity monitoring. (November 2021) - Zubair, H.T.; Rifiat, R.; Oresegun, Adebiyi; Hamidi, F.; Othman, J.; Khairina, M.D.; Basaif, A.; Ibrahim, S.A.; Abdul-Rashid, H.A.; Bradley, D.A.
Abstract: Currently existing low-level gamma-ray monitoring and measurement devices in the oil and gas and minerals beneficiations industries have several operational limitations, typically including an inability to be operated in an intrinsically safe mode, restrictions in making remote measurements, and an inability to operate in aqueous or high temperature environments. Herein, characterization is made of an optical fiber system based on a LYSO:Ce scintillator, investigated at dose rates and contamination levels comparable to that in dealing with NORM. The measurements were calibrated against a Geiger Muller (GM) pancake counter. The scintillators produce radioluminescence (RL), propagating in the optical fiber waveguide to the photodetection system, providing real-time, remote and intrinsically safe radiation measurements of NORM and other low-level gamma emissions. The response has been found to be dependent on the orientation of the scintillator axis with respect to the source centre. The LYSO:Ce scintillator has been found to be responsive to naturally radioactive sources, tested using monazite and xenotime offering in-contact dose rates down to 20 μSv/h. The measurements were found to be comparable to that of the GM based measurements, further providing intrinsically safe RL remote capabilities, the study pointing to the potential use of scintillation based optical fiber dosimetry systems for NORM and low gamma-ray level measurement in a variety of industrial scenarios. Highlights: Fiber optic coupled radiation sensor for NORM sample dose rate measurement. Sub-cm LYSO:Ce scintillator diameter. Sensitivity of 45 cpm/μSv/h during remote measurements (Cs-137). Probe is intrinsically safe, and resistant to water and electromagnetic interference.